Knowledge Management (KM) PractÄ±ces of the RetaÄ±l Industry in CamarÄ±nes Norte, PhÄ±lÄ±ppÄ±nes: A DescrÄ±ptÄ±ve QuantÄ±tatÄ±ve AnalysÄ±s - Mabeza, MA. Reina Ayende (APMBA (Asia Pacific Management and Business Application), 2022)
This study was conducted to ascertain the Knowledge Management (KM) practices of the retail industry, utilizing the quantitative descriptive research design. Using survey within the Philippines border the findings revealed that the majority of the retail industries in the province were highly understand the concept of Knowledge Management. Among its four major components the retail industries have the highest level of awareness towards the component of people, whereas, on the level of application, it is on the component of the strategy. While on customers' needs and satisfaction, KM strongly contributed to the retail industry and help uplift business operation and performance as well as long-term sustainability. It is concluded that by embracing Knowledge Management in business operations, the status of retail industry would rise up. The formulation of a centralized Knowledge Management system and collaboration to the government agency like the Department of Trade and Industry (DTI) will steadfast the growth of the retail industry in the province of Camarines Norte, Philippines.